Pemberdayaan Penyandang Disabilitas oleh Sheltered Workshop Peduli “Sambung Roso” di Desa Simbatan Kecamatan Nguntoronadi Kabupaten Magetan - Astutik, Sindi; Nawangsari, Ertien Rining (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2023)
People with disabilities are people who have privileges that make them different from normal people. Even though they are different, persons with disabilities have the right to receive empowerment like other citizens. Magetan Regency is one of the areas that has shelter for persons with disabilities, namely the Sheltered Workshop Peduli (SWP) “Sambung Roso”. Empowerment is carried out by providing training to make splashed batik to persons with disabilities. The purpose of this study was to find out how the empowerment of persons with disabilities by SWP "Sambung Roso" in Simbatan Village, Nguntoronadi District, Magetan Regency. The research method used is descriptive qualitative. The focus of this research uses the theory of community empowerment from Dedeh Maryani which consists of five principles, namely (i) the principle of equality, (ii) the principle of participation, (iii) the principle of self-sufficiency or independence and (iv) the principle of sustainability. The results of this study indicate that SWP "Sambung Roso" has achieved success in empowering persons with disabilities in Simbatan Village, Nguntoronadi District, Magetan Regency.